Articel The Language Function in the Dou Sandik “Praise and Worship” Tradisional of Biak Numfor Speech Community, Papua: A Linguistic Theology Study - Hugo Warami; Sintje Latuputty (RIRAI Publisher, 2022)
This article aims to uncover the use of theological language in the Dou Sandik tradition of Biak Numfor speech community. Grammatical theology is a theory that is able to show a human life in relation to God, and the uses of language and its set of game rules. This study uses two approaches, namely (1) a theoretical approach and (2) a methodological approach. The theoretical approach is an exploration of linguistic (grammatical) theological theory, while the methodological approach is a descriptive approach with an explanatory dimension. From the perspective of linguistic (grammatical) theology, this study seeks to apply scientific principles to linguistic data, as well as to adapt the steps of scientific studies in other fields of science. This study follows the procedures (1) the stage of providing data, (2) the stage of data analysis, and (3) the stage of presenting the results of data analysis. This study focuses on the efforts to reveal the